Moving the needle on racial disparity: COVID-19 vaccine trust and hesitancy. Issue 1 (3rd January 2022) - Lin, Cheryl; Tu, Pikuei; Terry, Thomas C.
Abstract: Health equity has grown in prominence during the pandemic. Racial disparities in COVID-19 infections and vaccine hesitancy (differences up to 26%) have generated concerns, research, and interventions with less-than-satisfactory results. Two longitudinal national surveys in the U.S. revealed previously overlooked patterns in the changes of COVID-19 vaccination intention across race/ethnicity. While White vaccine acceptance bounced back to the March 2020 level (65%) a year later, minority (except Asians) responses continued to lag and fluctuated with greater volatility. Though Hispanics' refusal aligned more with Blacks, the ratio of Hispanics willing to vaccinate was similar to Whites, even intermittently went above. Further, the magnitude and direction of changes varied by race at specific times (e.g., launch of Operation Warp Speed, reports of high vaccine efficacy in clinical trials or FDA approval), indicating subgroups react differently to events and thus require timely identification of driving factors for dynamic communications to encourage uptake. We also briefly reviewed the historical background of distrust in medicine and health authorities, including the Tuskegee Syphilis Study that led to the Belmont Report regulating human subject research and severe adverse reactions from the 1976 mass vaccination against the H1N1 swine flu. These examples, perpetuating inequity in the present healthcare system, and logistical barriers illustrate the contextual complexity and importance of instilling confidence in vaccines among the minority population.